KEANEKARAGAMAN KEPITING BIOLA PADA KAWASAN HUTAN MANGROVE DESA KARIMUNTING KECAMATAN SUNGAI RAYA KEPULAUAN KABUPATEN BENGKAYANG - Hanafi, Hanafi; Anwari, M Sofwan; Yani, Ahmad (JURNAL HUTAN LESTARI, 2020)
Karimunting Village is a coastal area that has a mangrove with contained several faunas in it, one of which is a fiddler crab. The fiddler crab is a Decapoda ordo and it is included in the Ocypodidae family. This study aims to collect data on the diversity of fiddler crabs in Karimunting Village. The method used in this study is a survey, while the sample is collected by applying the transect line with a purposive sampling technique. The transect line is 500 m length, with a total of three lanes. There are ten plots of 1x1 meter in size in each transect lines to pick up fiddler crabs. Fiddler crabs species were found in 6 species, namely Uca paradussumieri, Uca annulipes, Uca forcipata, Uca rosea, Uca crassipes and Uca tetragonon. The Shannon-Winner species diversity index (H') of fiddler crabs in 1st and 2nd lanes both are categorized medium, while in the 3rd lane is categorized low. The range of values H'=0,3-1,5. The value of species abundance index (Xi) ranges from 3-16.6 ind/m2. The value of evenness index (e) ranges from 0,72 to 0,84. The dominance index value (C) ranges from 0,3 to 0,5 categorized as the absence of the dominant species of fiddler crab. Comparison of species similarity index (IS) for each lane is categorized differently, for the 1st and 2nd lane the index is 91% and categorized as having high species similarity, then in 2nd and 3rd lane the index is 75% and categorized as having a medium species similarity, whereas the index for 1st and 3rd is 60%, therefore it is categorized as having low species similarity.Keyword: Diversity, Fiddler Crab, Karimunting Village